Uso de las tecnologías de la información y comunicación y comprensió lectora en estudiantes del segundo grado de secundaria Institución Educativa Mariscal Oscar Raymundo Benavides, distrito de Iquitos 2022 - Amaringo Caballero, Diana (2023)
The objective of the research was: to determine the relationship between the use of ICT and reading comprehension in second grade students of the Mariscal Oscar Raymundo Benavides Educational Institution in the district of Iquitos, in the year 2022. The study was of the type confirmatory, with a non-experimental descriptive - correlational cross-sectional design, made up of a population of 535 students and a sample of 224 students selected through the stratified method by proportional and simple random allocation, who were administered two questionnaires to measure the variables study. The results obtained on the level of use of ICT in the study sample, allowed us to determine that of 100% (n=224 students), 61.6% (n=138) reported a High level; 26.3% (n=59) a Medium level; and 12.1% (n=27) a Low level, respectively. Regarding the level of reading comprehension, it was determined that of 100% (n=224 students), 15.2% (n=34) obtained a level in Beginning; 66.5% (n=149) in Process; and 18.3% (n=41) in Expected Achievement, respectively. The inferential analysis using Spearman's Rho statistical test, with a confidence level of 95%, and a significance level ? = 0.05 (p < 0.05), allowed us to conclude that there is a significant relationship between the use of ICT and reading comprehension in second grade secondary school students from the study sample, thus verifying the validity of the general research hypothesis posed (p = 0.0000, p < 0.05). The inferential analysis of the relationship between the dimensions of the use of ICT and reading comprehension, allowed to determine that there is a significant relationship between the pedagogical dimension of the use of ICT and reading comprehension in second grade students of the secondary level of the sample of study, which confirmed the validity of specific hypothesis 1 (p = 0.0000, p < 0.05). t was determined that there is a significant relationship between the technological dimension of the use of ICT and reading comprehension in second grade students of the study sample, thus verifying the validity of specific hypothesis 2 (p = 0.0000, p <0.05). Finally, it was determined that there is a significant relationship between the communicative dimension of the use of ICT and reading comprehension in second grade students of the study sample, thus verifying the validity of specific hypothesis 3 (p = 0.0000, p < 0.05).